Influence of the particle parameters on the stability of magnetic dopants in a ferrolyotropic suspension - Appel, Ingo; Behrens, Silke (Journal of magnetism and magnetic materials, 2017)
The doping of liquid crystals with magnetic nanoparticles increases the magnetic susceptibility and the sensitivity to small magnetic fields. This offers interesting possibilities for controlling optical properties via external magnetic fields. The stabilization of magnetic nanoparticles in the liquid crystalline host, however, is challenging, since magnetic dipolar interactions and LC-mediated forces may result in their aggregation and even phase separation. So far, only few groups have investigated the long-term stability of these systems. In the present study, a set of magnetic iron oxide nanoparticles with different particle size, shape and surface properties was synthesized by thermal decomposition or co-precipitation. The magnetic nanoparticles were further integrated in a model liquid crystalline host (i.e., the lyotropic system potassium laurate/1-decanol/water) to investigate the effect of the different particle parameters on the stability of the resulting ferrolyotrope.